Funkcja autoprezentacyjna jako dominanta perlokucyjna form agresji werbalnej (na przykładzie komentarzy Pawła Zarzecznego „Krótko i na temat”) - Siekiera, Rafał (Acta Universitatis Lodziensis. Folia Linguistica, 2010)
The article studies means of verbal aggression, used by Paweł Zarzeczny in his commentaries “Shortly and about”, as part of process of creating the journalist’s occupational image. The publicist applies wide range of aggressive language behavior, from evident forms of aggression (such as insults or negative assessments), through camouflaged means of verbal aggression using comicality (among other things jokes, plays on words, irony) to hidden forms of aggression using intertextual manipulations (citations, analogies, stereotypes). All highly mentioned endeavors are purely manipulative and autopresentation (not the discreditation) is their predominating function. As proved in the article, Paweł Zarzeczny inscribes himself to a general trend in media for gaining publicity at the cost of someone else’s image.